2018
DOI: 10.1177/1938640018791017
|View full text |Cite
|
Sign up to set email alerts
|

Hemiarthroplasty Versus Total Joint Arthroplasty for Hallux Rigidus: A Systematic Review and Meta-analysis

Abstract: Level IV: Systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…The highest level of evidence supporting interposition arthroplasty are 3 retrospective case-control studies. A similar conclusion was published by Stibolt et al, 17 who determined, in a systematic review assessing the outcomes of hemi and total joint arthroplasty for hallux rigidus, that the highest level of evidence supporting arthroplasty is again a retrospective case-control study. The only other level I study available in the literature assessing surgical options for hallux rigidus other than the one identified by the current review 9 was a randomized controlled trial assessing the outcomes of arthrodesis and total replacement arthroplasty by Gibson et al 19 This puts the current evidence available for a PVA implant in perspective, as overall the evidence regarding surgical treatment for hallux rigidus is limited in its quality.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The highest level of evidence supporting interposition arthroplasty are 3 retrospective case-control studies. A similar conclusion was published by Stibolt et al, 17 who determined, in a systematic review assessing the outcomes of hemi and total joint arthroplasty for hallux rigidus, that the highest level of evidence supporting arthroplasty is again a retrospective case-control study. The only other level I study available in the literature assessing surgical options for hallux rigidus other than the one identified by the current review 9 was a randomized controlled trial assessing the outcomes of arthrodesis and total replacement arthroplasty by Gibson et al 19 This puts the current evidence available for a PVA implant in perspective, as overall the evidence regarding surgical treatment for hallux rigidus is limited in its quality.…”
Section: Discussionsupporting
confidence: 73%
“…Regarding surgical treatment for hallux rigidus in particular, there are multiple systematic reviews of the literature evaluating different surgical modalities. 3,17,18 In an article reviewing the evidence for interposition arthroplasty, Patel et al 18 identified 15 publications, of which 80% were level IV evidence. The highest level of evidence supporting interposition arthroplasty are 3 retrospective case-control studies.…”
Section: Discussionmentioning
confidence: 99%
“…28 Another showed that MTP-1 hemiarthroplasty may improve postoperative pain and function to a greater extent than total hemiarthroplasty. 42 Metatarsal erosion can be taken into discussion in conversion arthrodesis.…”
Section: Discussionmentioning
confidence: 99%